Legal rules on patent exploitation and management for innovation in Vietnamese universities - Nguyen, Phan Quoc; Mai, To Nhat (Edelweiss Applied Science and Technology, 2024)
According to the World Intellectual Property Organization (WIPO), universities are the cradles of creating new knowledge and technology, therefore, the management and exploitation of patent in higher education institutions plays a very important role in today's new context. Managing and exploiting patent brings many important benefits to lecturers, students, graduate students and scientists. It helps protect ideas and research from misappropriation, creates opportunities for commercialization and income from intellectual property rights protection, promotes collaboration and technology transfer, and enhances the university's reputation and brand. This article will help increase the university understanding and awareness of the importance of the governance and exploitation of patent as well as propose specific measures to help strengthen governance and exploitation activities.